A Rare Case of Dural Tail Sign in the Patient with Glioblastoma Multiforme: A Case Report - Risdiansyah Risdiansyah; Kusuma Eko Purwantari; Viskasari P Kalanjati; Rahadian I Susilo (Universitas Airlangga, 2023)
Highlight: A dural tail sign was found in T1W1-MR-images with contrast of a patient with glioblastoma multiforme. Glioblastoma multiforme as a grade IV malignancy of the astrocytes' glioma, the dura mater can be infiltrated and shown as DTS, although rarely reported. ABSTRACT Introduction: The dural tail sign (DTS), which is rarely seen in patients with glioblastoma multiforme (GBM), is reported here. This sign is generally found as a manifestation of meningioma due to the reactive changes of the tumor’s invasion. Case: A 61-year-old Javanese man presented with a gradually worsening headache two months prior to hospital admission. He also suffered from paralysis of his right extremities. His complete blood tests and clinical chemistry were within normal limits. A head CT scan showed a large mass near the convexity of the brain in the left parietal lobe, along with edema and a shift of the midline structures to the right. This was confirmed on the T1W1 MR images with contrast, where DTS was clearly shown. Following surgical resection and tumor excision, histopathology analysis revealed GBM with malignant cell infiltration to the dura in the vicinity of the neoplasm. Conclusion: Here we showed a DTS in GBM as a malignant infiltration marker into the dura